2017
DOI: 10.1111/ejn.13550
|View full text |Cite
|
Sign up to set email alerts
|

Chemogenetic enhancement of functional recovery after a sciatic nerve injury

Abstract: Designer receptors exclusively activated by designer drugs (DREADDs) are chemogenetic tools used to modulate neuronal excitability. We hypothesized that activation of excitatory (Gq) DREADD by its designer ligand, clozapine-N-oxide (CNO), would increase the excitability of neurons whose axons have been transected following peripheral nerve injury, and that this increase will lead to an enhanced functional recovery. The lateral gastrocnemius (LG) muscle of adult female Lewis rats was injected unilaterally with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 40 publications
3
19
0
Order By: Relevance
“…Such a change in excitability might occur whether or not the motoneurons were actually caused to fire by afferent stimulation. Indeed, in recent evidence from our laboratory, we conclude that subthreshold increases in motoneuron excitability may be sufficient to enhance motor axon regeneration (Jaiswal & English, ). In the current experiments, selective activation of sensory neurons via optical stimulation clearly enhanced the regeneration of sensory axons but did not affect the regeneration of motor axons (neither increased nor decreased).…”
Section: Discussionmentioning
confidence: 78%
“…Such a change in excitability might occur whether or not the motoneurons were actually caused to fire by afferent stimulation. Indeed, in recent evidence from our laboratory, we conclude that subthreshold increases in motoneuron excitability may be sufficient to enhance motor axon regeneration (Jaiswal & English, ). In the current experiments, selective activation of sensory neurons via optical stimulation clearly enhanced the regeneration of sensory axons but did not affect the regeneration of motor axons (neither increased nor decreased).…”
Section: Discussionmentioning
confidence: 78%
“…The simplest explanation for this chemogenetic enhancement of regeneration is that activation of the Gq DREADD using CNO resulted in an increase in the excitation of the injured neurons, leading to enhanced elongation of regenerating axons—a form of activity-dependent enhancement. In a previous study, we found that background EMG activity was not increased by CNO treatment of rats induced to express hM3Dq in motoneurons [ 14 ], leading us to conclude that activation of these modified muscarinic acetylcholine receptors produced an excitation of these neurons that was sub-threshold. Alternatively, constitutive expression of inhibitory DREADDs has been shown to induce CNO independent functional changes in sensory neurons [ 27 ].…”
Section: Discussionmentioning
confidence: 97%
“…Binding of CNO, or its major active metabolite, n-desmethylclozapine [ 9 , 10 , 11 ], to an excitatory (hM3Dq) DREADD results in activation of a Gq pathway [ 12 ] and neuronal excitation [ 13 ]. In an earlier report [ 14 ], we showed that significant enhancement of axon regeneration was found with CNO treatment in rats induced to express hM3Dq in motoneurons by retrograde adeno-associated viral transduction. Because the CNO treatments did not increase spontaneous electromyographic (EMG) activity, we concluded that DREADD activation must have produced a sub-threshold excitation in the transduced motoneurons, and that this level of excitation was sufficient to promote axon regeneration.…”
Section: Introductionmentioning
confidence: 86%
“…LLC., Tokyo, Japan) was dissolved in saline (Otsuka Pharmaceutical Co. LTD., Tokyo, Japan). Dosage of CNO was determined as described previously 28,29 . At 90 min after i.p.…”
Section: Methodsmentioning
confidence: 99%